Determination of deuterium depth profiles in fusion-relevant wall materials by nanosecond LIBS. (August 2017) - Suchoňová, M.; Veis, P.; Karhunen, J.; Paris, P.; Pribula, M.; Piip, K.; Laan, M.; Porosnicu, C.; Lungu, C.; Hakola, A.
Highlights: Comparison of method SIMS and LIBS for depth profile for D retention in AlWD and BeWD samples Ablation rate characteristic in the different samples (AlW, BeW with and without implantation of D). Study of possibility of using Aluminium as a proxy of Beryllium during the fusion experiments. Abstract: The ablation and fuel-retention characteristics of aluminum–tungsten (AlW) and beryllium–tungsten (BeW) samples have been determined using Laser Induced Breakdown Spectroscopy (LIBS) and compared to results obtained using Secondary Ion Mass Spectrometry (SIMS). The measurements have been made both at vacuum (of the order of 10 −4 Pa) and at 50 Pa of argon to especially enhance the intensities of the spectral lines of H and D. For reliable evaluation of the ablation rate of the samples the electron density ne and temperature Te of the LIBS plasma have been determined with the help of selected of spectral lines of Be, Al, and W. The electron density ne has been obtained from Stark broadening lines of Al I (308.7 nm and 394.4 nm) and Be I (457.3 nm) and Te from the Saha–Boltzmann plot using W I and W II spectral lines having a higher value of the energy of upper states in order to prevent the influence of self-absorption on the results. The results indicate similar ablation characteristics between AlW (AlWD) and BeW (BeWD) samples but the inclusion of deuterium in the coating increases the ablation rate by a factor of 10 for both sample types. Concerning fuel retention more than one order of magnitude less D is retained in the AlWD sample than in BeWD. In the presence of background argon, the H and D lines were stronger and more easily distinguishable. This is a positive sign considering the real application in ITER where LIBS measurements are foreseen to be done during maintenance breaks. However the higher pressure gave a better signal, it is still far from the measurement conditions planned for ITER which need to be tested separately.